The Influence of Learning Models Problem-Based Learning on Pancasila Education Learning Outcomes for Grade IV Students SDN 2 Pandanarum, Banjarnegara Regency - Galih Budiarto (UM Purwokerto Press, 2025)
The background of this research is because of the many real problems that arise in the life of society, nation and state. This is due to several factors such as the education system, environmental influences and mistakes in the use of technology so quickly. This research aims to improve students' ability to solve problems that arise in real life. This quantitative research uses an experimental approach that aims to determine whether there is an influence of the problem-based learning model on the learning outcomes of students in Pancasila Education learning in grade IV of SD Negeri 2 Pandanarum. The sample in this study is grade IV students of SD Negeri 2 Pandanarum as an experimental class and grade IV students of SD Negeri 1 Pandanarum as a control class. The learning experiment class by applying the problem-based learning model, while the control class by applying conventional learning. The data collection technique uses documentation, questionnaire and test techniques. The hypothesis test in this study used a t-test preceded by a Kolmogorov-Smirnov normality test and a homogeneity test using Levene's test. This data test was carried out using the help of SPSS 23 with a significance level of 5%. Based on the results of inferential statistical analysis, it was obtained that there was a positive influence between the problem based learning model on student learning outcomes with a sig value. 0.000 and 0.001 < 0.05.